Environmentally-friendly conductive cotton fabric as flexible strain sensor based on hot press reduced graphene oxide. (January 2017) - Ren, Jiesheng; Wang, Chaoxia; Zhang, Xuan; Carey, Tian; Chen, Kunlin; Yin, Yunjie; Torrisi, Felice
Abstract: A flexible conductive cotton fabric was demonstrated by formulation and deposition of a graphene oxide (GO) dispersion onto a cotton fabric by vacuum filtration. The deposited GO amount was controlled by the concentration and volume of the GO dispersion. The GO was reduced by a hot press method at 180 °C for 60 min, and no chemical reductant was needed in both the deposition and reduction processes. The carbon-oxygen ratio increased from 1.77 to 3.72 after the hot press reduction. The as-prepared flexible conductive cotton fabric showed a sheet resistance as low as 0.9 kΩ/sq. The sheet resistance of the conductive cotton fabric only increased from ∼0.9 kΩ/sq to ∼1.2 kΩ/sq after 10 washing cycles, exhibiting good washability. The conductive cotton fabric showed viability as a strain sensor even after 400 bending cycles, in which the stable change in the electrical resistance went from ∼3500 kΩ under tensile strain to ∼10 kΩ under compressive strain. This cost-effective and environmentally-friendly method can be easily extended to scalable production of reduced GO based flexible conductive cotton fabrics.